Fishes of the Western North Atlantic. - Bigelow, Henry Bryant, 1879-1967; Pérez Farfante, Isabel; Schroeder, William C. (William Charles), 1895- (Memoir (Sears Foundation for Marine Research), 1948)
This volume, the first of a series, describes the lancelets, the hagfishes and the lampreys, and those most interesting animals, the sharks. It has been written on the premise that it should be useful to those in many walks of life--to those casually or vitally interested in the general phenomena of life in our waters, to the sportsman whose interests are closely associated with pleasure and relaxation, to the fisherman whose livelihood depends upon knowledge of where fishes are gathered together, as well as to the amateur ichthyologist and the professional scientist. Special stress has been given to the relationship of the fishes to ourselves--in most cases this relationship is to man's advantage, but the present volume also carries this theme in reverse--some sharks will attack man! The reason for the present series of volumes is to correlate the contents of the rich storehouse of knowledge relating to the fishes that live in the waters of the western North Atlantic.